Atrial standstill in the newborn: a case report - O. Yu. Dzhaffarova; I. V. Plotnikova; L. I. Svintsova (Российский кардиологический журнал, 2021)
Introduction. Persistent atrial standstill is a rare syndrome characterized by absence of mechanical and electrical atrial activity. The article presents a unique case of atrial standstill in the newborn patient with tachyarrhythmia.Brief description. The first manifestation of atrial standstill in the patient was heart failure (HF) manifestations and wide-complex tachycardia according to electrocardiography, which was identified as ventricular tachycardia. At the local outpatient clinic, the child was prescribed with antiarrhythmic therapy (AAT), which decreased heart rate. Three months later, a transesophageal electrophysiological study was carried out in our center in order to determine the arrhythmia origin. A multiform idioventricular rhythm with a heart rate of 46-119 beats per min was diagnosed, atrial pacing spike (A waves) was not recorded. Given bradyarrhythmia, hemodynamic abnormalities on echocardiography (significant atrial enlargement, decreased contractility), the patient, in order to prevent the risk of sudden cardiac death, underwent implantation of single chamber pacemaker in VVIR mode and bipolar ventricular lead. Anticoagulant therapy was prescribed. After 6-month follow-up, relief of HF symptoms and an increase in left ventricular contractile function was noted.Discussion. Timely diagnosis and implantation of pacemakers allowed avoiding AAT and minimizing the HF symptoms. Continuous ventricular pacing and anticoagulant therapy are important in HF prevention.